2022
DOI: 10.3389/fphar.2022.826716
|View full text |Cite
|
Sign up to set email alerts
|

Sporoderm-Broken Spores of Ganoderma lucidum Sensitizes Ovarian Cancer to Cisplatin by ROS/ERK Signaling and Attenuates Chemotherapy-Related Toxicity

Abstract: Although platinum-based chemotherapeutics such as cisplatin are the cornerstone of treatment for ovarian cancer, their clinical application is profoundly limited due to chemoresistance and severe adverse effects. Sporoderm-broken spores of Ganoderma lucidum (SBSGL) have been reported to possess antitumor effects. However, the function and mechanism of SBSGL and its essential composition, ganoderic acid D (GAD), in the cisplatin therapy on ovarian cancer have yet to be investigated. Here, we investigated the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Speculatively, this effect may be attributed to KF1 's ability to reduce the generation of reactive oxygen species (ROS) through its antioxidation properties and inhibit the activation of the ERK signaling pathway, consequently diminishing arsenic‐induced skin damage. A recent study has shown that antioxidants actively combat cell damage by effectively reducing ROS production and preventing the activation of the ERK signaling pathway 56 . This research provides experimental evidence to enhance our understanding of KF1 's potential in the prevention and treatment of arsenic‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Speculatively, this effect may be attributed to KF1 's ability to reduce the generation of reactive oxygen species (ROS) through its antioxidation properties and inhibit the activation of the ERK signaling pathway, consequently diminishing arsenic‐induced skin damage. A recent study has shown that antioxidants actively combat cell damage by effectively reducing ROS production and preventing the activation of the ERK signaling pathway 56 . This research provides experimental evidence to enhance our understanding of KF1 's potential in the prevention and treatment of arsenic‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study has shown that antioxidants actively combat cell damage by effectively reducing ROS production and preventing the activation of the ERK signaling pathway. 56 This research provides experimental evidence to enhance our understanding of KF1's potential in the prevention and treatment of arsenic-induced apoptosis. In addition, this finding raises an important question for future research, prompting the evaluation of KF1's application value in arsenic detoxification through animal experiments or human intervention studies.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Cen et al reported that combining Ganoderma lucidum polysaccharide with cisplatin reduced tumor growth and improved intestinal damage caused by cisplatin via inhibiting ROS-mediated ERK signaling against ovarian cancer. Besides, Ganoderma lucidum polysaccharide significantly sensitized cells to cisplatin in ovarian cancer 18 . Zhao et al showed that Ganoderma lucidum polysaccharide and cisplatin caused cell cycle arrest in the G2/M phase and caused apoptosis by activating caspase 3 and p53 up-regulation.…”
Section: Discussionmentioning
confidence: 94%
“…Cen et al evaluated the anticancer potential of Ganoderma lucidum against ovarian cancer. The obtained results exhibited the reactive-induced species-induced activation of the ERK pathway [ 146 ]. Thimmaraju et al studied the anti-tumor effect of polysaccharide (HUP-2) isolated from Hypsizygus ulmarius .…”
Section: Mushrooms As a Source Of Anticancer Agentsmentioning
confidence: 99%